A user's guide to the brain : perception, attention, and the four theaters of the brain - Ratey, John J., 1948- (New York : Pantheon Books, 2001)
Examines the basic structure and chemistry of the brain, looking at what advances in the neurosciences have revealed about different aspects of the brain's functioning and flexibility.
Includes bibliographical references (p. [381]-384) and index.
Booklist.
Choice.
Wilson's Senior High School.
Adult
Keywords: Brain -- Popular works; Neurochemistry -- Popular works; Neuropsychology -- Popular works; Brain; Psychology